2008
DOI: 10.1007/s11764-008-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the needs of young breast cancer survivors at the 5 year milestone: can a short-term, low intensity intervention produce change?

Abstract: The intervention was related to greater knowledge related to breast cancer, and increased report of physical activity. The program was not related to changes in reported diet or family communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 58 publications
(40 reference statements)
3
74
0
Order By: Relevance
“…James et al 52 reported that perceived social support for a healthier diet was significantly higher for people with crc than for the general population, although the higher support was not associated with healthier behaviours. Another study by Bloom et al 53 reported that breast cancer patients with large social networks were more likely than those with small networks to report increased physical activity after a socio-educational intervention. Because family and friends were frequently cited as resources and might directly affect the lifestyle behaviours of people with cancer, we argue that lifestyle resources and programs should consider involving and providing information not only to people with cancer, but also to their friends and family.…”
Section: Considerations For Designing Lifestyle Resourcesmentioning
confidence: 99%
“…James et al 52 reported that perceived social support for a healthier diet was significantly higher for people with crc than for the general population, although the higher support was not associated with healthier behaviours. Another study by Bloom et al 53 reported that breast cancer patients with large social networks were more likely than those with small networks to report increased physical activity after a socio-educational intervention. Because family and friends were frequently cited as resources and might directly affect the lifestyle behaviours of people with cancer, we argue that lifestyle resources and programs should consider involving and providing information not only to people with cancer, but also to their friends and family.…”
Section: Considerations For Designing Lifestyle Resourcesmentioning
confidence: 99%
“…Five-years post cancer diagnosis is a very important Bmilestone^in the life of every cancer survivor [29], as it represents the end of a period of high risk for cancer recurrence and the beginning of a lower risk period [30,31]. To our knowledge, the current study is the first to investigate the association between the receipt of SCP and SCD during the two very important time intervals in the survivorship continuum, less than (short-term) and more than (long-term) 5 years from cancer diagnosis [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility study will allow an additional mode of bringing exercise and nutrition wellness into these survivors' households. The current study has shown that utilization of an online, at-home exercise based program and education on essential nutrients and their role in the body can provide a more feasible way of implementing health lifestyle and behavior changes to improve quality of life [29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%